Celebrations of the heart - Rice, Helen Steiner. frey50 (Grand Rapids, Mich. : F.H. Revell, 2001)
It's the season for love--all year around. Times of festivity give us opportunities to bask in the warmth of love shared by friends and family. Helen Steiner Rice captures the essence of these special moments in Celebrations of the Heart. This beautiful collection of peotry is the perfect holiday or appreciation gift and a source of inspiration for teachers and church leaders to read on special occasions. Create warm memories by sharing Rice's poems for Easter, Mother's Day and Father's Day, weddings and anniversaries, Thanksgiving, Christmas, birthdays, even retirement!
Keywords: Christian Poetry -- American